Acknowledging the needs of computer-assisted translation tools users: the human perspective in human-machine translation - AnneMarie Taravella; Alain O. Villeneuve (JoSTrans: The Journal of Specialised Translation)
The lack of translation specialists poses a problem for the growing translation markets around the world. One of the solutions proposed for the lack of human resources is automated translation tools. In the last few decades, organisations have had the opportunity to increase their use of technological resources. However, there is no consensus on the way that technological resources should be integrated into translation service providers (TSP). The approach taken by this article is to set aside both 100% human translation and 100% machine translation (without human intervention), to examine a third, more realistic solution: interactive translation where humans and machines co-operate. What is the human role? Based on the conceptual framework of information systems and organisational sciences, we recommend giving users, who are mainly translators for whom interactive translation tools are designed, a fundamental role in the thinking surrounding the implementation of a technological tool.